Pengaruh Kualitas Pelayanan terhadap Kepuasan Pelanggan pada Coffee Shop Cold N Brew Medan - Johannes Mario Nainggolan; Agus Mariani Saragih; Erwinsyah Simanungkalit; Jumjuma Jumjuma; Nursiah Nursiah (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
In the midst of the development of an increasingly urban and lifestyle-oriented society, the Coffee Shop business is one of the fastest growing businesses. Coffee shops are no longer just a place to drink coffee, but also a place to socialize, work, study, or just relax. In this increasingly competitive coffee shop business, service quality is the key to differentiating one coffee shop from another. Good service quality can create a positive experience for customers and encourage them to return as indicators of customer satisfaction. This study aims to determine the effect of service quality on customer satisfaction at Coffee Shop Cold n Brew Medan. This study uses a quantitative approach with the analysis technique simple linear regression, respondents as a data source as many as 98 people. Data collection using questionnaire techniques. The results showed that service quality has a significant effect on customer satisfaction. The implication of this research is the importance of Coffee Shop to continue to improve its service quality in order to maintain and increase customer satisfaction and have competitiveness in the Coffee Shop industry.